2020
DOI: 10.1002/acr2.11135
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Intravenous Anakinra Infusion to Calm the Cytokine Storm in Macrophage Activation Syndrome

Abstract: Objective The objective of this study was to report the benefit of a therapeutic approach consisting of intravenous (IV) continuous anakinra (recombinant human interleukin‐1 receptor antagonist) infusions in treating severely ill adult patients with secondary hemophagocytic lymphohistiocytosis or macrophage activation syndrome (MAS). Methods A retrospective chart review of five patients treated at Regions Hospital from 2016 to 2019 was conducted. Demographic, clinical, and laboratory characteristics and outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
149
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(164 citation statements)
references
References 39 publications
1
149
0
9
Order By: Relevance
“…Anakinra, an IL-1 receptor antagonist that blocks the biologic activity of IL-1, is a promising agent in this setting since it has already been shown to be effective in severe sepsis complicated by CRS macrophage activation syndrome [29, 30]. Recently Monteagudo et al [31] reported 5 cases of a cytokine storm (2 with an identified viral trigger) in which continuous intravenous anakinra infusion resulted in prompt improvement in laboratory and clinical parameters. There are limited data with specific IL-1 blockers in patients with COVID-19.…”
Section: Cytokine-targeting Therapiesmentioning
confidence: 99%
“…Anakinra, an IL-1 receptor antagonist that blocks the biologic activity of IL-1, is a promising agent in this setting since it has already been shown to be effective in severe sepsis complicated by CRS macrophage activation syndrome [29, 30]. Recently Monteagudo et al [31] reported 5 cases of a cytokine storm (2 with an identified viral trigger) in which continuous intravenous anakinra infusion resulted in prompt improvement in laboratory and clinical parameters. There are limited data with specific IL-1 blockers in patients with COVID-19.…”
Section: Cytokine-targeting Therapiesmentioning
confidence: 99%
“…Promisingly, IL-1 blockade was associated with decreased mortality ( 141 ). More recently, a study by Monteagudo et al showed that IL-1 inhibitors were also effective in calming cytokine storm in hemophagocytic lymphocytosis patients ( 142 ). Huet et al also published a cohort study of 52 critically ill SARS-CoV-2 patients given Anakinra (an IL-1-inhibitor) and supportive care, while a control group of 44 patients received only supportive care.…”
Section: Treatment Protocolsmentioning
confidence: 99%
“…Anakinra was shown to increase the survival rate in patients with sepsis who meet the criteria for MAS, and who had liver dysfunction and disseminated intravascular coagulation [8]. This drug has also been used to treat several rare syndromes characterized by hyperin ammation mediated by the altered regulation of cytokine responses [9] [10]. Several studies have reported the bene ts of anakinra as an initial treatment for patients with hyperin ammation associated with severe SARS CoV-2 infection [11] [12] [13] [14], although these studies did not focus on patients who failed to respond to corticosteroid pulses or tocilizumab therapy alone or in combination.…”
Section: Introductionmentioning
confidence: 99%